2020
DOI: 10.1016/j.psj.2020.05.051
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococci in poultry intestines: a comparison between farmed and household chickens

Abstract: Both pathogenic as well as nonpathogenic species of staphylococci have been reported in poultry, but these studies have not compared staphylococcal flora of both farmed and household broiler chickens. Staphylococci from farmed (n = 51) and household chicken intestines (n = 43) were isolated and tested for resistance to antimicrobials, presence of resistance genes, and inhibitory activity against other bacteria; correlation of resistance phenotype and genotype was also evaluated. At least 12 staphylococcal spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 37 publications
2
14
0
Order By: Relevance
“…[20] found Staphylococcus species in 24.75% of examined chicken farms. All Staphylococcus isolates in the period from 2014 to 2018 were examined for antibiotic resistance against 14 antibiotics, and our results reported high resistance against tetracycline, streptomycin, ampicillin, and nalidixic acid, followed by penicillin, doxycycline, trimethoprim, and chloramphenicol all over the five years, and these results were the same to those mentioned in studies of other countries such as Indonesia, Pakistan, South Africa, and Nigeria [8,[37][38][39], respectively, while the results of tetracycline and chloramphenicol detected in [8] and the results of ampicillin, ciprofloxacin, enrofloxacin, and streptomycin examined in [20] were lower than what we found in our study.…”
Section: Salmonella Species Isolatessupporting
confidence: 86%
“…[20] found Staphylococcus species in 24.75% of examined chicken farms. All Staphylococcus isolates in the period from 2014 to 2018 were examined for antibiotic resistance against 14 antibiotics, and our results reported high resistance against tetracycline, streptomycin, ampicillin, and nalidixic acid, followed by penicillin, doxycycline, trimethoprim, and chloramphenicol all over the five years, and these results were the same to those mentioned in studies of other countries such as Indonesia, Pakistan, South Africa, and Nigeria [8,[37][38][39], respectively, while the results of tetracycline and chloramphenicol detected in [8] and the results of ampicillin, ciprofloxacin, enrofloxacin, and streptomycin examined in [20] were lower than what we found in our study.…”
Section: Salmonella Species Isolatessupporting
confidence: 86%
“… 2002 ; Syed et al. 2020 ). Staphylococci are found in animal products as well as in the environment – in dirt, dust, air, and water.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies reported similar results for the frequency of erm genes in poultry [28,39]. A study by Syed et al investigated the resistance of staphylococci in poultry intestines and reported a lower frequency of resistance to macrolides and lincosamides, but the ermC gene was also the most prevalent [47]. In the same study, resistance to tetracycline was detected in more than half of the isolates encoded by the tetK and tetM genes [47].…”
Section: Discussionmentioning
confidence: 62%
“…A study by Syed et al investigated the resistance of staphylococci in poultry intestines and reported a lower frequency of resistance to macrolides and lincosamides, but the ermC gene was also the most prevalent [47]. In the same study, resistance to tetracycline was detected in more than half of the isolates encoded by the tetK and tetM genes [47]. In our study, resistance to tetracycline was detected in 85.3% of the isolates, including all S. sciutri, S. urealyticus and S. haemolyticus, and in 25 out of 36 S. lentus, which was similar to the findings of other studies [28,31,48].…”
Section: Discussionmentioning
confidence: 99%